The Optimization of Learning Media Through Augmented Reality to Improve Student Learning Comprehension - Saeful Anwar; Tati Suprapti; Yoga Nugraha; Arif Rinaldi Dikananda (Institut Teknologi Dirgantara Adisutjipto, 2026)
This study presents the development and evaluation of an Augmented Reality (AR) based learning media optimized to enhance students’ comprehension of camera architecture concepts. The AR system was developed using Unity 3D integrated with Vuforia SDK, implementing a marker-based AR approach to ensure stability and compatibility with limited mobile device specifications. The system architecture consists of a mobile AR client, image-marker recognition module, 3D visualization engine, and learning interaction layer designed based on multimedia learning principles and cognitive load theory. A five-stage development framework was employed: planning, material collection, assembly, implementation, and evaluation. The AR media was applied in an undergraduate informatics course involving 30 students, using a one-group pretest–posttest design. Learning outcomes were analyzed using paired t-tests, Wilcoxon tests, normalized gain, and effect size measurements. Results show significant improvements across all cognitive dimensions (p < 0.001), with very large effect sizes (dz = 3.13) and a moderate normalized gain (g = 0.42). The findings indicate that AR provides strong practical impact on higher-order cognitive skills, particularly application and analysis, while highlighting limitations related to measurement instrument validity, absence of a control group, and limited sample generalizability, which will be addressed in future research through experimental comparison and extended system performance testing.